Research on Interior Design of Traditional Chinese Medicine Clinics under the Translation of Regional Cultural Symbols - Li Yanyan; Jiang Jinwen (SHS Web of Conferences)
In a multicultural context, as an important carrier of traditional medicine and culture, the interior design of traditional Chinese medicine urgently needs to achieve the creative translation of cultural symbols in the process of modernization. Based on the theory of “transliteration of regional cultural symbols”, this study systematically explores the extraction methods, reconstruction logic and spatial expression mechanism of cultural elements in the interior design of traditional Chinese medicine clinics. By analyzing typical regional cultural symbols, this study aims to provide a theoretical basis and practical reference for the contemporary transformation of traditional Chinese medicine Spaces, and to promote the collaborative innovation of regional culture and medical building design.